Comparative study of plant diversity around water towers in hyper-arid areas (Adrar, Algeria) - Souddi, Mohammed; Bouallala, M’hammed (Biodiversity: Research and Conservation, 2024)
Water is a vital compound that determines the life of all organisms, but is often deficient, especially in hyper-arid areas. The rapid development and expansion of modern irrigation systems in these areas has created favourable environments for many plant species adapted to extreme aridity. In this study, to compare plant diversity in the vicinity of 6 water towers in hyper-arid areas, at each site we conducted 5 floristic surveys on the basis of subjective sampling. The floristic data were analysed using biodiversity and statistical parameters. We recorded there 43 species of 22 families, with a good representation of the Poaceae (18.6%) and Asteraceae (14.0%). According to Raunkiaer’s classification, the plant cover is mainly composed of therophytes (41.8%), i.e. annual species that complete their development cycle within one growing season. The spectrum of various types of dispersal shows the dominance of flora by anemochorous species (70.7%). A chorological analysis of the vegetation in the area revealed the importance of the Saharo-Arabian element (41.9%), which confirms its adaptation to the environment of the hyper-arid zones of the Sahara. The analysis of abundance classes revealed the existence of 10 rare species (18.1%), 3 very rare species (4.9%), and one fairly rare species (1.3%). In conclusion, the environments surrounding water towers in hyper-arid areas require adequate management measures to preserve biodiversity in Saharan environments.